China Internet Development Report 2017 Translated by Peng Ping - Chinese Academy of Cyberspace Studies; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
This book provides a comprehensive review of China's Internet development in the past 23 years since the country's first access to the Internet, especially since the 18th National Congress of the Communist Party of China. It offers a systematic account of China's experience in Internet development and governance, and establishes and presents China's Internet Development Index System, covering network infrastructure, information technology, digital economy, e-governance, cyber security, and international cyberspace governance.
Overview -- Comprehensive Improvement of China's Network Infrastructure -- Breakthroughs have been made in Information Technology -- Digital Economy has become the New Engine for Economic Growth -- E-administration makes Governmental Service more Efficient and Transparent -- Clean Cyberspace -- Cyber Security Capacity is being Improved -- Active Participation in International Cyberspace Governance -- Benefits of the Internet to the People -- Prospect of China's Internet Development -- Appendix: Events of China's Internet Development -- Afterword.
Keywords: Telecommunication; Signal processing; Industrial Management; Technology; History; Communications Engineering, Networks; Signal, Speech and Image Processing .; Industrial Management; History of Technology